2018
DOI: 10.1038/s41598-017-18613-2
|View full text |Cite
|
Sign up to set email alerts
|

Developing genome-wide SNPs and constructing an ultrahigh-density linkage map in oil palm

Abstract: Oil palm (Elaeis guineensis Jacq.) is the leading oil-producing crops and the most important edible oil resource worldwide. DNA markers and genetic linkage maps are essential resources for marker-assisted selection to accelerate genetic improvement. We conducted RAD-seq on an Illumina NextSeq500 to discover genome-wide SNPs, and used the SNPs to construct a linkage map for an oil palm (Tenera) population derived from a cross between a Deli Dura and an AVROS Pisifera. The RAD-seq produced 1,076 million single-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 46 publications
(69 reference statements)
0
14
0
1
Order By: Relevance
“…The bacterial culture produced three families of ACL namely iturin, surfactin and fengycin with strong anti-fungal activity against Ganoderma (Pramudito et al, 2018). Similarly, Lee et al (2018a) characterised phenazine and phenazine-1-carboxylic acid isolated from Pseudomonas aeuruginosa with anti-microbial activity against G. boninense. Another interesting study conducted by Surendran et al (2018a, b) reported that naturally occurring phenolics acids such as benzoic acid and salicylic acids were able to suppress the enzymatic secretion of Ganoderma spp.…”
Section: Sustainable Upstreammentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial culture produced three families of ACL namely iturin, surfactin and fengycin with strong anti-fungal activity against Ganoderma (Pramudito et al, 2018). Similarly, Lee et al (2018a) characterised phenazine and phenazine-1-carboxylic acid isolated from Pseudomonas aeuruginosa with anti-microbial activity against G. boninense. Another interesting study conducted by Surendran et al (2018a, b) reported that naturally occurring phenolics acids such as benzoic acid and salicylic acids were able to suppress the enzymatic secretion of Ganoderma spp.…”
Section: Sustainable Upstreammentioning
confidence: 99%
“…In this respect, the earlier publications of the genome (Singh et al, 2013a, b) and epigenome (Ong-Abdullah et al, 2015) have continued to fuel further research in oil palm. Bai et al (2018a) developed genome-wide single nucleotide polymorphisms (SNP) and constructed an ultrahigh-density linkage map using the revolutionary restriction-site associated DNA sequencing (RAD-seq) technology. This technology allowed higher frequency of SNP discovery of at least more than 10 000 as compared to the 2000 to 3500 SNP from previous studies (Pootakham et al, 2015;Bai et al, 2017), was modified for use on a highly heterogenous oil palm breeding population.…”
Section: Advancing With Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting sequence reads are then aligned either de novo or to a reference genome, to generate RAD loci that are interrogated for single nucleotide polymorphisms (SNPs). These in turn provide the basis for diverse applications from linkage and association mapping [3, 4], through elucidating population structure and patterns of introgression [5, 6] to quantifying inbreeding depression [7].…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm ( E. guineensis ) is the most valuable vegetable oil crop that contributes significantly to the food requirements of the world's growing population which is expected to reach 240 million tons by 2050 . Fruit mesocarp can produce palm oil up to 90% of dry weight, thus representing the highest lipid content compared with other oilseeds .…”
Section: Introductionmentioning
confidence: 99%